Penggunaan Media Bahan Alam untuk Meningkatkan Kemampuan Berhitung pada Anak Usia 5-6 Tahun - Briyantika Puji Lestari; Nisa'el Amala (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2021)
Activities of mathematics for children early age creativity so that children can have the ability to count and implement it in their future lives, especially in problem-solving skills. The importance of numeracy skills to be introduced to children from an early age is because the children are in a pleasant atmosphere and have a sense of security and freedom of expression. This problem took children in the Dharma Wanita Ketanon Kindergarten institution, 13 children with cognitive achievement related to numeracy skills, only two children received BSH while nine children were in the MB category and 2 BB children. The needs analysis found learning facilities that can foster children'sinterest in achieving numeracy skills. The research carried out is Classroom Action Research by applying three cycles. The results of this study are accepted and can find that the first percentage of completeness is 30.7%, in the second percentage of completeness is 61.5%, and in the third cycle, the percentage of completeness is 84.6%.